Investigation of Structural and Optical Properties of Dilute GaAsBi and InGaAsBi Semiconductor Nanostructures Grown by Molecular Beam Epitaxy - Alhassni, Amra (2023)
This thesis investigates the optical and structural properties of GaAs1-xBix thin epitaxial layers and self-assembled InGa(Bi)As quantum dots (QDs) grown on conventional (100) GaAs substrates by Molecular Beam Epitaxy (MBE). The GaAs1-xBix epilayers were grown at different substrate temperatures. The InGa(Bi)As QDs were formed via the Stranski-Krastanov (S-K) growth mode using bismuth as a surfactant.